Magnetic ureteral stent removal without cystoscopy: a randomized controlled trial - Rassweiler-Seyfried, Marie-Claire; Michel, Maurice Stephan; Ritter, Manuel; Honeck, Patrick (Journal of endourology, 2017)
Introduction: Ureteral stenting is a common procedure in urology. The cystoscopic removal of Double-J stents (DJ) causes unpleasant side effects with a negative impact on patient's quality of life. The aim of our study was to evaluate this newly developed magnetic DJ and compare it with a standard DJ regarding quality of life with indwelling DJs as well as discomfort during the removal.Material and Methods: The magnetic DJ (Blackstar, Urotech [Achenmühle, Germany]) is a standard 7F ureteral stent with a small magnetic cube fixed through a string on the loop of the distal part of the stent. For DJ removal, a special catheter-like retrieval instrument with a magnetic tip is inserted, the two magnets connect and the retrieval instrument is removed with the DJ. We first tested this DJ in 20 cases. Afterward we evaluated 40 consecutive cases that required a DJ placement after ureterorenoscopy in a prospective randomized manner. The quality of life was assessed by the ureteral stent symptom questionnaire. A visual analogue scale was used to document the pain by DJ removal.Results: There was a significant difference regarding the pain location with the indwelling DJ (p = 0.038). The maximum pain was located in the lower abdomen and/or around the bladder (48%) with the magnetic DJ, whereas the standard DJ caused flank pain in 54% of the patients. The mean time for the magnetic DJ removal including preparation and cleaning as for a transurethral catheter insertion was 9.55 [7-14] minutes, whereas the mean time for the cystoscopic DJ removal was 21.35 [18-30] minutes. The pain caused by the removal of the magnetic DJ was significantly less than that caused by the cystoscopic DJ removal (p = 0.019).Conclusion: The discomfort caused by the indwelling magnetic DJ is comparable with that caused by the standard DJ. However, the magnetic DJ removal is less painful and faster.
Gesehen am 12.07.2018